Taking care of healthcare workers during COVID-19 pandemic: does plastic surgery have a role? Taking care of healthcare workers during COVID-19 pandemic - Giardino, Francesco Ruben; Cuomo, Roberto; Sisti, Andrea; Han, Jingjian; Giuseppe, Nisi; Grimaldi, Luca (Acta Biomedica Atenei Parmensis, 2020)
Background: The massive use of personal protective equipment is required by the medical and paramedical staff of the COVID-19 dedicated departments. This often causes painful pressure injuries. The aim of this study is to value the use of anesthetic cream and collagen veil masks for the treatment of pain. We also evaluated the possible psychological impact on healthcare workers involved in the emergency, which is currently a hot topic in the worldwide literature. Materials and Methods: We applied lidocaine idrochloride 5% cream and a collagen veil mask respectively  before and after each work shift. We evaluated the improvement of pain symptoms through VAS assessments. We used a modified Maslach burnout inventory as well to evaluate the psychological impact of our treatments on  healthcare workers. Results: A significant reduction of pain was detected within the first 3 days, but this was not significant over the long period (10 days). Otherwise, we saw a significant improvement of the psychological assessment (p